Integrative Influence of Innovation Management, Operational Efficiency, and Marketing Strategy on Business Performance: The Mediating Role of Absorptive Capacity in Warmindo SMEs of Bekasi - Ade Saputra; Muhammad Rafi Rahmadani; Dimas Suhendi; Abdullah Hasan Bustomi (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2025)
This research is motivated by the need for Warmindo MSMEs to increase competitiveness amidst digital disruption and market dynamics by strengthening internal capabilities. The study aims to analyze the influence of innovation management, operational efficiency, and marketing strategy on business performance with absorptive capacity as a mediating variable. The study uses a quantitative approach with the Structural Equation Modeling (SEM) method assisted by AMOS 24. Data were obtained through a survey of 500 owners or managers of Warmindo MSMEs in Bekasi Regency who have been running their businesses for at least two years. The results show that innovation management has a positive and significant effect on absorptive capacity, while operational efficiency has no direct effect on absorptive capacity or business performance, but has a significant effect on marketing strategy. Absorption capacity is proven to have a positive effect on marketing strategy and business performance and mediates the relationship between innovation management and business performance. Conversely, marketing strategy does not show a significant direct effect on business performance. These findings confirm that absorptive capacity is an important mechanism linking innovation to improved business performance in Warmindo MSMEs. The implications of the research show the importance of strengthening digital literacy, developing knowledge management systems, and supporting policies that encourage organizational learning so that MSMEs are more adaptive, competitive, and sustainable.